A Study on the Differences in Regional Attractiveness of Recognized Local Stories - Park, Jeongbae; Hwang, Changha (International Journal of Membrane Science and Technology, 2023)
Regional visit satisfaction of visitors can be increased by raising the regional attractiveness of recognized local stories. The purpose of current study is to explore the internal suitability of a confidence level for analyzing impacts to recognized local stories’ regional attractiveness empirically and the Cronbach’s alpha for the questions related to recognized local stories elements of a regional attractiveness showed good internal suitability with 0.905 and 0.874. As a result of proceeding with a regression analysis for verifying a study model, the power (the factors which are uniqueness, portrayal, understandability, and sensibility) of the recognized stories suggested from the study model and the regional attractiveness (the factors which are education, significance, and experientiality) are selected as they affect significant impacts. Local brand creations and expansions can be important cultural values for vitalizing a local economy via the study of the relationships (differences) between recognized local stories and regional attractiveness. In this study, the validity of each measure’s variable used for the study’s basic static analysis and each scale construction, and the credibility whether the measures variables are consisting of latent variables consistently were verified. And it is experimented if the recognized story’s regional attractiveness relationships (differences) can be applied to this study by suggesting the hypothesis adoption status via regression analysis verifying causal impacts between variables. These were very meaningful in this study. Because if we study that regional story content elements are very effective in regional activation by increasing regional attractiveness for visitors then it might be able to be systemized theoretically and be used for practical businesses.